Molecular genotyping of mycobacterium tuberculosis associated with extrapulmonary tuberculosis - Ayub, Nur Izzah Farakhin (2015)
Recent advances in molecular typing provide a robust tool to analyse the heterogeneity of Mycobacterium tuberculosis strains as well as their transmission patterns. In the first attempt study from Kelantan, Malaysia, the frequency and diversity of M. tuberculosis genotypes associated with extrapulmonary tuberculosis (EPTB) were performed using spoligotyping. Genotyping results were compared with the SITVIT Web, a largest M. tuberculosis molecular markers international database containing 7104 spoligotype patterns worldwide. The results showed that 74.6 % (n = 44) of the isolates were grouped under previously defined shared international type (SIT) numbers while 25.4 % (n = 15) did not have any SIT numbers, thus designated as orphan strains. The largest lineage comprised of 23 isolates (38.9 %) belonging to the Beijing lineage. Present study suggested frequency of M. tuberculosis lineages are related more on geographical settings rather than sites of infection. Bulk of the strains associated with EPTB in the study population also caused by new strain that is not available in the SITVIT Web database. The study may serves as a reference material for further genotyping studies on estimating the actual prevalence of M. tuberculosis associated with EPTB in Malaysia generally